180 EFFECTS OF MECHANICAL VENTILATION ON GENES THAT REGULATE LUNG DEVELOPMENT IN NEWBORN MICE. (1st January 2005) - Jacobson, B.; Bland, R.
Abstract : Failed formation of alveoli and lung capillaries is a key histological feature of neonatal chronic lung disease (CLD). CLD typically afflicts preterm infants with incompletely developed lungs that have been exposed to prolonged mechanical ventilation with O2 -enriched gas. As lung septation and angiogenesis occur mainly after term birth in mice, we did studies to see if positive-pressure mechanical ventilation, with or without added O2, would alter lung expression of genes that regulate alveolar and lung vascular development in newborn mice. We studied 4 groups of 6-8 pups that were 2-4d old and weighed 2.8±0.7g. Group 1 (MV-O2 ) had a tracheotomy with ketamine-xylazine anesthesia, followed by mechanical ventilation with 40% O2 for 8h at 60 breaths/min (bpm), peak inflation pressure (PIP) 17±1 cmH2O, end-expiratory pressure (PEEP) 1 cmH2O. Group 2 (Control-O2 ) had sham surgery and then breathed spontaneously in 40% O2 for 8h. Group 3 (MV-air) had a tracheotomy followed by mechanical ventilation with air for 8h at 60 bpm, PIP 16 ± 1 and PEEP 1 cmH2O. Group 4 (Control-air) had sham surgery and then breathed room air for 8h. Lungs from 4-6 pups/group were frozen in liquid N2 and stored at -80(C for later gene microarray analysis and quantitative RT-PCR to measure mRNA for genes considered important in lung development (Vascular Endothelial Growth Factor A, VEGF-A, and its receptor, VEGF-R2; Tenascin-C, TN-C; and Lysyl Oxidase, LO). Lungs from some pups in each group were fixed by tracheal instillation of 10% formalin for histology, which showed no structural differences or evidence of injury among the 4 groups of mice. Gene microarrays and qRT-PCR showed significantly less lung expression of VEGF, VEGF-R2 and TN-C, and more LO in Group 1 (MV-O2 ) compared to Group 2 (Control-O2 ). Parallel studies on lungs of pups that breathed air showed significantly less VEGF, but not VEGF-R2 or TN-C, and more LO in Group 3 (MV-air) compared to Group 4 (Control-air). These findings indicate that a prolonged period of cyclic lung inflation with O2 -enriched gas at a critical stage of development, even without apparent lung injury, may adversely affect pulmonary expression of genes that are known to be important in regulating formation of alveoli and lung blood vessels. This work has important implications for studying mechanisms involved in the pathogenesis of CLD.